Liquid grinding aid for high-alkali cement and method for its preparation

CN118459140BActive Publication Date: 2026-11-03JIN YU JIE NENG KE JI (TIAN JIN) YOU XIAN GONG SI +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410506648.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2026-11-03
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

Existing grinding aids have limited grinding effects on high-alkali cement and cannot meet the high strength requirements of high-alkali cement in projects such as bridges, highways, railways and airport runways.

Method used

A liquid grinding aid composed of modified polyol amine esters, glycerol, sodium chloride and hydroxycarboxylate in a specific ratio improves grinding efficiency, optimizes particle size distribution and promotes hydration process, improves the morphology of hydration products, and thus enhances the strength of high-alkali cement.

Benefits of technology

It significantly improves the grinding efficiency and strength of high-alkali cement, reduces production costs, and optimizes the morphology and particle size distribution of hydration products, thus promoting the hydration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004810510540000101
    Figure BDA0004810510540000101
  • Figure BDA0004810510540000111
    Figure BDA0004810510540000111
Patent Text Reader

Abstract

The application relates to a liquid grinding aid for high-alkali cement and a preparation method thereof, and relates to the field of grinding aids, wherein raw materials used by the application include the following components in parts by weight: modified polyol amine ester 15-25 parts, glycerol 7-12 parts, sodium chloride 0.5-1.5 parts, hydroxyl carboxylic acid salt 3-6 parts and water 60-70 parts. The application has the effects of improving the grinding aid effect on high-alkali cement, optimizing the particle size distribution of the high-alkali cement, promoting the hydration process, improving the morphology of the hydration product, and thus improving the strength of the high-alkali cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of grinding aids, and in particular to a liquid grinding aid for high-alkali cement and a method for preparing the same. Background Technology

[0002] Cement grinding is a crucial step in cement production. Grinding machinery grinds cement clinker to a suitable particle size to meet the requirements for cement paste setting and hardening. During the grinding process, the specific surface area of ​​the material particles increases, and their surfaces become charged due to the breaking of chemical bonds. These charged particles tend to attract each other, forming clumps or adhering to the grinding equipment, reducing grinding efficiency and increasing energy consumption. To improve cement grinding efficiency and reduce energy consumption, grinding aids are typically added to the cement. Grinding aids can significantly increase cement output per hour, cement strength at various ages, improve its fluidity, greatly reduce electrostatic adsorption and balling phenomena during grinding, and reduce the tendency for ultrafine particles to re-agglomerate during grinding.

[0003] Currently, cement grinding aids are usually made by compounding alkanolamines, polyols, and inorganic salts in a certain proportion. These cement grinding aids can not only improve the grinding effect, but also enhance the cement by promoting the cement hydration process.

[0004] High-alkali cement is characterized by its rapid hydration rate and high strength, making it frequently used in projects requiring high strength, such as bridge construction, highway paving, large factory buildings, equipment foundations, and industrial and civil construction. Furthermore, with the expanding applications of high-alkali cement, even higher strength requirements are being placed on it, for example, in emergency repairs of bridges, highways, railways, and airport runways. However, experiments have shown that existing grinding aids for high-alkali cement have limited grinding effects, and the strength of the cement cannot meet these higher performance requirements. Summary of the Invention

[0005] To address the aforementioned technical problems, this application provides a liquid grinding aid for high-alkali cement and its preparation method.

[0006] In the first aspect, this application provides a liquid grinding aid for high-alkali cement, which adopts the following technical solution: A liquid grinding aid for high-alkali cement, the raw materials used include the following components in parts by weight: 15-25 parts of modified polyol amine ester, 7-12 parts of glycerol, 0.5-1.5 parts of sodium chloride, 3-6 parts of hydroxycarboxylate and 60-70 parts of water.

[0007] By adopting the above technical solution, this application uses a mixture of modified polyol amine esters, glycerol, sodium chloride, and hydroxycarboxylate in a specific ratio range to fully leverage the synergistic effect of multiple components. By improving the grinding effect on high-alkali cement, optimizing the particle size distribution of high-alkali cement, and increasing the dissolution rate of hydration products, the hydration process is promoted. At the same time, the morphology of hydration products is improved, making the ground high-alkali cement more compact and increasing the hydration rate, thereby effectively improving the strength of high-alkali cement.

[0008] Specifically, glycerol and modified polyol amine esters, as the main grinding aid components in liquid grinding aids, can reduce the agglomeration of cement particles by lowering the surface energy of cement particles and reducing electrostatic adsorption, thereby improving the grinding effect, optimizing the particle size distribution of high-alkali cement, and thus improving the strength of high-alkali cement.

[0009] Furthermore, glycerol not only helps disperse other components in liquid grinding aids, improving the dispersibility of modified polyol amine esters and facilitating the formation of a complete adsorption layer on the surface of cement particles, but also allows hydroxycarboxylate to fully exert its effect on improving the morphology of hydration products, thereby further improving the grinding effect.

[0010] This application also adds sodium chloride to the liquid grinding aid, which can improve the solubility of iron and aluminum ions generated during the hydration of high-alkali cement through electrolyte action, thereby fully exerting a synergistic effect with the modified polyol amine ester in promoting cement hydration. Furthermore, the addition of sodium chloride can also improve the ionic strength of the liquid grinding aid, making the ions more mobile, and together with glycerol, improve the dispersibility of other components.

[0011] Preferably, the modified polyol amine ester comprises triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester, acrylic acid, initiator and chain transfer agent in a molar ratio of (13-17):(5-8):(18-22):(0.05-0.15):(0.03-0.12).

[0012] By adopting the above technical solution, this application involves the free radical polymerization of triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester, and acrylic acid under the action of an initiator and a chain transfer agent to generate a modified polyol amine ester. The carboxyl groups in the acrylic acid increase the number of polar groups in the modified polyol amine ester, which is beneficial for the adsorption of the modified polyol amine ester on the surface of cement particles, improving the stability of the adsorption layer and thus further improving grinding efficiency. The long carbon chains in the isobutylene alcohol polyoxyethylene ether fatty acid ester wet the fresh interface, improving the flowability of the powder. Furthermore, the isobutylene alcohol polyoxyethylene ether fatty acid ester has high surface activity, thereby increasing the adsorption rate of the modified polyol amine ester on the surface of cement particles, making the adsorption layer more stable, further reducing the surface energy of the cement particles, and thus further reducing the agglomeration of high-alkali cement particles. Modified polyol amine esters further reduce the surface tension of cement particles by forming a highly stable adsorption layer and improve the flowability of powder through the wetting effect of long carbon chains, thereby improving their grinding aid effect on high-alkali cement, optimizing the particle size distribution of cement particles, making high-alkali cement more compact, promoting the hydration process, and thus improving the strength of high-alkali cement.

[0013] Optionally, the preparation method of the modified polyol amine ester includes the following steps: S1. Disperse triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester and chain transfer agent in water, stir and mix to obtain a mixed solution with a concentration of 50-55 wt%. S2. Heat the mixed solution obtained in step S1 to 75-85℃, and simultaneously add an acrylic acid solution with a concentration of 60-63wt% and an initiator solution with a concentration of 15-18wt% to it. Stir the reaction for 3.5-4 hours to obtain a modified polyol amine ester solution. S3. The modified polyol amine ester solution in step S2 is filtered to obtain a crude modified polyol amine ester product, and the crude modified polyol amine ester product is washed and dried to obtain a modified polyol amine ester.

[0014] Preferably, in step S2, the mixed solution is heated to 80°C.

[0015] By employing the above technical solution, triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester, and a chain transfer agent are dispersed in water to obtain a mixed solution. Since acrylic acid has high reactivity and readily undergoes self-polymerization, it is dissolved separately in water to obtain an acrylic acid solution. The mixed solution is heated to 85-95°C, and the acrylic acid solution and initiator solution are simultaneously added dropwise while stirring to carry out a free radical polymerization reaction. Acrylic acid and isobutylene alcohol polyoxyethylene ether fatty acid ester are grafted onto triisopropanolamine maleate as monomers to obtain a modified polyol amine ester.

[0016] In this application, the temperature of the mixed solution was optimized, which improved the conversion rate of the free radical polymerization reaction, resulting in better stability of the adsorption layer formed by the modified polyol amine ester, thereby improving the grinding aid effect of the modified polyol amine ester.

[0017] Preferably, the isobutylene alcohol polyoxyethylene ether fatty acid ester is isobutylene alcohol polyoxyethylene ether palmitate.

[0018] By adopting the above technical solution, the isobutylene alcohol polyoxyethylene ether fatty acid ester selected in this application is isobutylene alcohol polyoxyethylene ether palmitate. Experimental data demonstrates that using palmitic acid in the esterification modification of isobutylene alcohol polyoxyethylene ether, compared to using oleic acid and myristic acid, can reduce the residue on the 45μm sieve of high-alkali cement by 1.1% and 1.3%, respectively, and increase the specific surface area by 9m², respectively. 2 / kg and 10m 2 / kg, the 3d flexural strength increased by 0.4MPa and 0.6MPa, respectively, and the 3d compressive strength increased by 1.2MPa and 1.9MPa, respectively. This indicates that the isobutylene alcohol polyoxyethylene ether palmitate obtained by esterification modification of isobutylene alcohol polyoxyethylene ether with palmitic acid has better surface activity than other fatty acids. The isobutylene alcohol polyoxyethylene ether palmitate makes the modified polyol amine ester have a better grinding aid effect.

[0019] Optionally, the preparation method of the isobutylene alcohol polyoxyethylene ether palmitate includes the following steps: I. Prepare a reaction solution by stirring and mixing isobutylene alcohol polyoxyethylene ether, palmitic acid and catalyst; II. The reaction solution obtained in step I is heated to 135-145℃ in an oil bath and subjected to vacuum distillation while stirring for 2.5-3.5 hours to obtain a crude product. The crude product is dried to constant weight to obtain isobutylene alcohol polyoxyethylene ether palmitate. The weight ratio of isobutylene polyoxyethylene ether, palmitic acid and catalyst is (12-18):(2-3):(0.1-0.15), and the catalyst is p-toluenesulfonic acid.

[0020] Preferably, in step II, the reaction solution is heated to 140°C.

[0021] By employing the above technical solution, isobutylene alcohol polyoxyethylene ether, palmitic acid, and catalyst are mixed uniformly, heated to the reaction temperature, and an esterification reaction is carried out. The reaction solution is then subjected to vacuum distillation to remove the water generated in the reaction, thereby increasing the esterification reaction rate. This application optimizes the reaction temperature of the esterification reaction, improves the esterification rate, and gives isobutylene alcohol polyoxyethylene ether palmitate high surface activity, thus enabling the adsorption layer formed by the modified polyol amine ester to have good stability.

[0022] Preferably, the hydroxycarboxylic acid salt is sodium gluconate.

[0023] By adopting the above technical solution, sodium gluconate has a good effect on improving the morphology of hydration products and thus enhancing the strength of high-alkali cement. Furthermore, experimental data have shown that, compared with sodium alginate or sodium citrate, using sodium gluconate in combination with modified polyol amine ester can increase the 3-day compressive strength of high-alkali cement by 1.8 MPa and 2 MPa, respectively, and the 3-day flexural strength by 0.6 MPa and 0.8 MPa, respectively. This indicates that sodium gluconate has a better effect on improving the strength of high-alkali cement than other hydroxycarboxylate salts.

[0024] Secondly, this application provides a method for preparing a liquid grinding aid for high-alkali cement, comprising the following steps: mixing and stirring modified polyol amine ester, glycerol, sodium chloride, hydroxycarboxylate and water to obtain a liquid grinding aid for high-alkali cement.

[0025] By employing the above technical solution, weighing each component according to the weight ratio, and mixing the components thoroughly, a liquid grinding aid for high-alkali cement is prepared. This preparation method is simple to operate, resulting in relatively stable performance of the liquid grinding aid.

[0026] Thirdly, this application provides an application of a liquid grinding aid for high-alkali cement: The liquid grinding aid used for high-alkali cement is added at a dosage of 0.04-0.06 wt% of the high-alkali cement during the high-alkali cement grinding process.

[0027] By adopting the above technical solution, the liquid grinding aid provided in this application has a high grinding aid effect and a good improvement effect on the performance of high alkali cement. It can achieve excellent results with a small dosage, thereby reducing the production cost of high alkali cement.

[0028] In summary, this application has the following beneficial technical effects: 1. The liquid grinding aid provided in this application fully leverages the synergistic effect among its components, thereby promoting the hydration process by improving the grinding effect on high-alkali cement and increasing the dissolution rate of hydration products. At the same time, it improves the morphology of hydration products, making the high-alkali cement more compact and thus enhancing its strength. 2. By carrying out free radical polymerization of triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester and acrylic acid, the stability of the adsorption layer formed by the modified polyol amine ester on the surface of cement particles is improved, the surface energy of cement particles is reduced, thereby improving the grinding effect of high alkali cement, optimizing the particle size distribution of cement particles, promoting the hydration process, improving the density of high alkali cement, and thus improving the strength of high alkali cement. Detailed Implementation

[0029] Material source Unless otherwise specified, all raw materials used in this application are commercially available products, specifically: Triisopropanolamine maleate was purchased from Jiangsu Shuangxiang Group; Palmitic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Acrylic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Ammonium persulfate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Dodecyl mercaptan was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Glycerol was purchased from Henan Shuangjie Chemical Co., Ltd. Sodium chloride was purchased from Shandong Zhengyu Chemical Technology Co., Ltd. Oleic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Sodium gluconate was purchased from Shandong Mingwei Chemical Co., Ltd. Sodium alginate was purchased from Hebei Pengyu Biotechnology Co., Ltd. Ammonium citrate was purchased from Hebei Pengyu Biotechnology Co., Ltd. Myristic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Isobutylene alcohol polyoxyethylene ether was purchased from Zhejiang Xinxin Chemical Co., Ltd. The cement clinker was purchased from Lingshou County Zeyan Mineral Products Co., Ltd., with the product number 221123 and an alkali content of 0.98%. The fly ash was purchased from Luetu Fine Chemicals Hebei Co., Ltd., and the fly ash type is F. The gypsum was purchased from Dingfeng Environmental Protection Technology Co., Ltd., and the gypsum type is building gypsum. The slag was purchased from Luetu Fine Chemicals Hebei Co., Ltd., and the slag type is S95.

[0030] Preparation Example 1.1 The preparation method of isobutylene alcohol polyoxyethylene ether palmitate includes the following steps: I. Place 180g of isobutylene polyoxyethylene ether, 20g of palmitic acid and 1.5g of p-toluenesulfonic acid into a round-bottom flask and stir to mix to obtain a reaction solution; II. Place the round-bottom flask in an oil bath, heat the reaction solution obtained in step I to 145°C, and use a vacuum pump to perform vacuum distillation on the reaction system in the round-bottom flask at a vacuum degree of -0.1 MPa. At the same time, stir the reaction for 2.5 h to obtain a crude product. Place the crude product in a vacuum drying oven and dry it to constant weight to obtain isobutylene alcohol polyoxyethylene ether palmitate.

[0031] Preparation Example 1.2 The preparation method of isobutylene alcohol polyoxyethylene ether palmitate includes the following steps: I. Place 120g of isobutylene polyoxyethylene ether, 30g of palmitic acid and 1g of p-toluenesulfonic acid into a round-bottom flask and stir to mix to obtain a reaction solution. II. Place the round-bottom flask in an oil bath, heat the reaction solution obtained in step I to 135°C, and use a vacuum pump to perform vacuum distillation on the reaction system in the round-bottom flask at a vacuum degree of -0.1 MPa. At the same time, stir the reaction for 3.5 h to obtain a crude product. Place the crude product in a vacuum drying oven and dry it to constant weight to obtain isobutylene alcohol polyoxyethylene ether palmitate.

[0032] Preparation Example 1.3 The difference from Preparation Example 1 is that in step II, the reaction solution obtained in step I is heated to 140°C.

[0033] Preparation Example 1.4 The difference from Preparation Example 1 is that in step II, the reaction solution obtained in step I is heated to 130°C.

[0034] Preparation Example 1.5 The difference from Preparation Example 1 is that in step II, the reaction solution obtained in step I is heated to 150°C.

[0035] Preparation Example 1.6 The difference from Preparation Example 1 is that in step I, the mass of isobutylene alcohol polyoxyethylene ether is 120g, the mass of palmitic acid is 40g, and the mass of p-toluenesulfonic acid is 0.5g.

[0036] Preparation Example 1.7 The difference from Preparation Example 1 is that in step I, the mass of isobutylene alcohol polyoxyethylene ether is 200g, the mass of palmitic acid is 20g, and the mass of p-toluenesulfonic acid is 0.2g.

[0037] Preparation Example 1.8 The difference from Preparation Example 1 is that palmitic acid in step I is replaced with oleic acid.

[0038] Preparation Example 1.9 The difference from Preparation Example 1 is that palmitic acid in step I is replaced with myristic acid.

[0039] Preparation Example 2.1 The preparation method of modified polyol amine esters includes the following steps: S1. Disperse 248.69g of triisopropanolamine maleate, 2000g of isobutylene alcohol polyoxyethylene ether fatty acid ester and 0.61g of dodecyl mercaptan in 2249.3ml of water and stir to obtain a mixed solution. S2. Dissolve 129.71g of acrylic acid in 86.5ml of water to obtain an acrylic acid solution. Dissolve 3.42g of ammonium persulfate in 19.4ml of water to obtain an initiator solution. Heat the mixed solution obtained in step S1 to 75°C and simultaneously add the acrylic acid solution and the initiator solution to it. Stir the reaction for 4 hours to obtain a modified polyol amine ester solution. S3. The modified polyol amine ester solution in step S2 is filtered to obtain a crude product, and the crude product is washed and dried to obtain the modified polyol amine ester. In step S1, the isobutylene alcohol polyoxyethylene ether fatty acid ester used is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.1.

[0040] Preparation Example 2.2 The preparation method of modified polyol amine esters includes the following steps: S1. Disperse 325.16g of triisopropanolamine maleate, 1250g of isobutylene alcohol polyoxyethylene ether fatty acid ester and 2.43g of dodecyl mercaptan in 1290.8ml of water and stir to obtain a mixed solution. S2. Dissolve 158.53g of acrylic acid in 93.1ml of water to obtain an acrylic acid solution. Dissolve 1.14g of ammonium persulfate in 5.2ml of water to obtain an initiator solution. Heat the mixed solution obtained in step S1 to 85℃ and simultaneously add the acrylic acid solution and the initiator solution to it. Stir the reaction for 3.5h to obtain a modified polyol amine ester solution. S3. The modified polyol amine ester solution in step S2 is filtered to obtain a crude product, and the crude product is washed and dried to obtain the modified polyol amine ester. In step S1, the isobutylene alcohol polyoxyethylene ether fatty acid ester used is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.1.

[0041] Preparation Example 2.3 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.2.

[0042] Preparation Example 2.4 The difference from Preparation Example 2.1 is that in step S2, the mixed solution obtained in step S1 is heated to 80°C.

[0043] Preparation Example 2.5 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.3.

[0044] Preparation Example 2.6 The difference from Preparation Example 2.1 is that in step S1, 191.27 g of triisopropanolamine maleate, 2500 g of isobutylene alcohol polyoxyethylene ether fatty acid ester, and 0.2 g of dodecyl mercaptan are dispersed in 1795.5 ml of water and stirred to obtain a mixed solution; in step S2, 108.9 g of acrylic acid is dissolved in 72.6 ml of water to obtain an acrylic acid solution, and 4.56 g of ammonium persulfate is dissolved in 25.8 ml of water to prepare an initiator solution.

[0045] Preparation Example 2.7 The difference from Preparation Example 2.1 is that in step S1, 382.54 g of triisopropanolamine maleate, 750 g of isobutylene alcohol polyoxyethylene ether fatty acid ester, and 3.04 g of dodecyl mercaptan are dispersed in 776.2 ml of water and stirred to obtain a mixed solution; in step S2, 180.15 g of acrylic acid is dissolved in 120 ml of water to obtain an acrylic acid solution, and 6.85 g of ammonium persulfate is dissolved in 38.9 ml of water to prepare an initiator solution.

[0046] Preparation Example 2.8 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.4.

[0047] Preparation Example 2.9 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.5.

[0048] Preparation Example 2.10 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.6.

[0049] Preparation Example 2.11 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether palmitate prepared in Preparation Example 1.7.

[0050] Preparation Example 2.12 The difference from Preparation Example 2.1 is that in step S2, the mixed solution obtained in step S1 is heated to 65°C.

[0051] Preparation Example 2.13 The difference from Preparation Example 2.1 is that in step S2, the mixed solution obtained in step S1 is heated to 95°C.

[0052] Preparation Example 2.14 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether oleate prepared in Preparation Example 1.8.

[0053] Preparation Example 2.15 The difference from Preparation Example 2.1 is that the isobutylene alcohol polyoxyethylene ether fatty acid ester used in step S1 is the isobutylene alcohol polyoxyethylene ether myristate ester prepared in Preparation Example 1.9.

[0054] Preparation Example 2.16 The difference from Preparation Example 2.1 is that in step S1, 325.16 g of triisopropanolamine maleate and 2.43 g of dodecyl mercaptan were dispersed in 327.6 ml of water and stirred to obtain a mixed solution.

[0055] Preparation Example 2.17 The difference from Preparation Example 2.1 is that: in step S2, an acrylic acid solution is not prepared, the mixed solution obtained in step S1 is heated to 75°C, and an initiator solution is added dropwise to it.

[0056] Example 1 Mix 15g of modified polyol amine ester, 12g of glycerol, 0.5g of sodium chloride, 3g of sodium gluconate and 60ml of water, and stir well to obtain a liquid grinding aid for high-alkali cement.

[0057] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0058] Example 2 Mix 25g of modified polyol amine ester, 7g of glycerol, 1.5g of sodium chloride, 6g of sodium gluconate and 70ml of water, and stir well to obtain a liquid grinding aid for high-alkali cement.

[0059] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0060] Example 3-18 The difference from Example 1 is that the modified polyol amine ester used is the modified polyol amine ester prepared in Preparation Examples 2.2-2.17.

[0061] Example 19 The difference from Example 1 is that sodium gluconate is replaced with sodium alginate.

[0062] Example 20 The difference from Example 1 is that sodium gluconate is replaced with sodium citrate.

[0063] Comparative Example 1 Mix 10g of modified polyol amine ester, 15g of glycerol, 0.3g of sodium chloride, 2g of sodium gluconate and 55ml of water, and stir well to obtain a liquid grinding aid for high-alkali cement.

[0064] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0065] Comparative Example 2 Mix 30g of modified polyol amine ester, 5g of glycerol, 2g of sodium chloride, 8g of sodium gluconate and 75ml of water, stir well to obtain a liquid grinding aid for high-alkali cement.

[0066] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0067] Comparative Example 3 Mix 15g of modified polyol amine ester, 0.5g of sodium chloride, 3g of sodium gluconate and 60ml of water, stir well to obtain a liquid grinding aid for high-alkali cement.

[0068] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0069] Comparative Example 4 Mix 15g of modified polyol amine ester, 12g of glycerol, 3g of sodium gluconate and 60ml of water, stir well to obtain a liquid grinding aid for high-alkali cement.

[0070] The modified polyol amine ester used was the modified polyol amine ester prepared in Preparation Example 2.1.

[0071] Comparative Example 5 The difference from Example 1 is that the modified polyol amine ester is replaced with triisopropanolamine maleate.

[0072] Application Example 1 According to the P.O42.5 cement mix proportion, 3.9 kg of cement clinker, 0.6 kg of slag, 0.25 kg of gypsum and 0.25 kg of fly ash were added to the test mill, and 0.04 wt% of the liquid grinding aid prepared in Example 1 was added to it. The milling was carried out for 10 min to obtain high alkali cement.

[0073] Application Example 2 According to the P.O42.5 cement mix proportion, 3.9 kg of cement clinker, 0.6 kg of slag, 0.25 kg of gypsum and 0.25 kg of fly ash were added to the test mill, and 0.06 wt% of the liquid grinding aid prepared in Example 1 was added to it. The milling was carried out for 10 min to obtain high alkali cement.

[0074] Application Example 3-21 The difference from Application Example 1 is that the liquid grinding aid used is the liquid grinding aid prepared in Examples 2-20.

[0075] Compare and contrast examples 1-5 The difference from Application Example 1 is that the liquid grinding aids used are the liquid grinding aids prepared in Comparative Examples 1-5.

[0076] Performance testing 1. Refer to the test methods in GB / T 26748-2011 "Cement Grinding Aids" and conduct performance tests on the high-alkali cement prepared in corresponding Case 1-21 and Comparative Application Case 1-5, and determine the specific surface area and 45μm sieve residue of the high-alkali cement.

[0077] 2. Referring to GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the 3-day flexural strength and 3-day compressive strength of cement mortar made with high alkali cement prepared in Application Examples 1-21 and Comparative Application Examples 1-5 were determined. Mortar meeting the consistency requirements was made into 40mm×40mm×160mm prism specimens and placed in a standard curing chamber with a constant temperature of 25℃ and a relative humidity of 95% for 3 days before testing.

[0078] The performance test results are shown in Table 1.

[0079] Table 1 Cement performance test results As shown in Table 1, the 45μm sieve residues in Examples 1-2 of this application were 13.2% and 12.7%, respectively, and the specific surface areas were 427 m², respectively. 2 / kg, 429m 2 The 3-day flexural strengths were 7.3 MPa and 7.4 MPa, respectively, and the 3-day compressive strengths were 39.3 MPa and 39.5 MPa, respectively. This indicates that the liquid grinding aid and the dosage of the liquid grinding aid provided in this application have a good grinding effect on high-alkali cement and enable high-alkali cement to have high strength.

[0080] The performance indicators of Application Example 3 are close to those of Application Example 1, indicating that the mixing ratio range of the liquid grinding aid provided in this application has a stable effect on improving the grinding effect and increasing the strength of high-alkali cement.

[0081] The performance indicators of Application Example 4 are close to those of Application Example 1, indicating that the ratio range of the modified polyol amine ester provided in this application has a stable effect on improving the grinding aid effect and increasing the strength of high alkali cement.

[0082] The performance indicators of Application Example 5 are similar to those of Application Example 1, indicating that the polyol amine ester ratio range provided by this application has a stable effect on improving the grinding aid effect and increasing the strength of high alkali cement.

[0083] In Application Example 6 of this application, the residue on the 45 μm sieve was reduced by 2.7% compared to Application Example 1, and the specific surface area was increased by 10 m². 2 / kg, the 3d flexural strength increased by 0.6MPa and the 3d compressive strength increased by 2.4MPa, indicating that the preferred temperature of 80℃ for preparing modified polyol amine ester provided in this application has a better effect in the provided temperature range of 75-85℃, further improving the grinding aid effect of liquid grinding aid and the strength of high alkali cement.

[0084] In Application Example 7 of this application, the 45 μm sieve residue was reduced by 2.5% compared to Application Example 1, and the specific surface area was increased by 8 m². 2 / kg, the 3d flexural strength increased by 0.5MPa and the 3d compressive strength increased by 2.5MPa, indicating that the preferred temperature of 140℃ for preparing isobutylene polyoxyethylene ether palmitate provided in this application has a better effect in the provided temperature range of 135-145℃, further improving the grinding effect of liquid grinding aid and the strength of high alkali cement.

[0085] In Application Example 8 of this application, the 45 μm sieve residue increased by 1.6% compared to Application Example 1, while the specific surface area decreased by 16 m². 2 / kg, the 3-day flexural strength decreased by 0.4 MPa, and the 3-day compressive strength decreased by 0.8 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 9 increased by 1.3%, and the specific surface area decreased by 11 m². 2 / kg, the 3d flexural strength decreased by 0.3MPa and the 3d compressive strength decreased by 0.6MPa, indicating that the proportion range of each component in the modified polyol amine ester provided in this application has a good effect on improving the grinding aid effect of liquid grinding aid and the strength of high alkali cement.

[0086] Application Example 10 of this application shows a 1.6% increase in sieve residue and a 16m² decrease in specific surface area compared to Application Example 1. 2 / kg, the 3-day flexural strength decreased by 0.4 MPa, and the 3-day compressive strength decreased by 0.8 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 1 increased by 1.6%, and the specific surface area decreased by 16 m². 2 / kg, the 3d flexural strength decreased by 0.4MPa and the 3d compressive strength decreased by 0.8MPa, indicating that the esterification rate was lower than the temperature range provided in this application when the temperature for preparing isobutylene polyoxyethylene ether palmitate was 130℃ and 150℃. This shows that the temperature range of the esterification reaction provided in this application has a good effect on improving the grinding aid effect and the strength of high alkali cement.

[0087] Application Example 12 of this application shows a 2.1% increase in sieve residue and a 22m² decrease in specific surface area compared to Application Example 1. 2 / kg, the 3-day flexural strength decreased by 0.4 MPa, and the 3-day compressive strength decreased by 1.7 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 1 increased by 1.9%, and the specific surface area decreased by 20 m². 2 / kg, the 3d flexural strength decreased by 0.2MPa and the 3d compressive strength decreased by 1.4MPa, indicating that the proportion range of each component in the isobutylene polyoxyethylene ether palmitate provided in this application has a good effect on improving the grinding aid effect and the strength of high alkali cement.

[0088] Application Example 14 of this application shows a 1.8% increase in sieve residue and a 18m² decrease in specific surface area compared to Application Example 1. 2 / kg, the 3-day flexural strength decreased by 0.8 MPa, and the 3-day compressive strength decreased by 1.2 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 1 increased by 2.2%, and the specific surface area decreased by 24 m². 2 / kg, the 3-day flexural strength decreased by 1.0 MPa, and the 3-day compressive strength decreased by 1.6 MPa. This indicates that the grinding aid effect of the modified polyol amine ester prepared at temperatures of 65℃ and 95℃ is lower than that of the modified polyol amine ester prepared within the temperature range provided in this application. This demonstrates that the temperature range provided in this application for preparing modified polyol amine ester has a good effect on improving the grinding aid effect of modified polyol amine ester and increasing the strength of high-alkali cement.

[0089] Application Example 16 of this application shows a 1.1% increase in sieve residue and a 9m² decrease in specific surface area compared to Application Example 1 with the 45μm sieve. 2 / kg, the 3-day flexural strength decreased by 0.4 MPa, and the 3-day compressive strength decreased by 1.2 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 17 increased by 1.3%, and the specific surface area decreased by 10 m². 2 / kg, the 3d flexural strength decreased by 0.6MPa and the 3d compressive strength decreased by 1.9MPa, indicating that the isobutylene polyoxyethylene ether palmitate provided in this application has a better effect on improving the strength of high alkali cement than isobutylene polyoxyethylene ether oleate and isobutylene polyoxyethylene ether myristate.

[0090] Application Example 18 of this application shows a 4.1% increase in sieve residue and a 30m² decrease in specific surface area compared to Application Example 1. 2 / kg, the 3-day flexural strength decreased by 0.9 MPa, and the 3-day compressive strength decreased by 2.2 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 1 increased by 4.4%, and the specific surface area decreased by 33 m². 2 / kg, the 3d flexural strength decreased by 1MPa and the 3d compressive strength decreased by 2.4MPa, indicating that the components of the modified polyol amine ester provided in this application have a good effect on improving the grinding aid effect and increasing the strength of high alkali cement.

[0091] Compared to Application Example 1, Application Example 20 of this application shows a 2% increase in 45μm sieve residue and a 19m² decrease in specific surface area. 2 / kg, the 3-day flexural strength decreased by 0.6 MPa, and the 3-day compressive strength decreased by 1.8 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 21 increased by 2.1%, and the specific surface area decreased by 20 m². 2 / kg, the 3d flexural strength decreased by 0.8MPa and the 3d compressive strength decreased by 2MPa, indicating that the sodium gluconate provided in this application has a better effect on improving the grinding aid effect of liquid grinding aids and the strength of high alkali cement compared with other hydroxycarboxylate salts.

[0092] Compared to Application Example 1, the residue of the 45μm sieve in this application increased by 2.9%, while the specific surface area decreased by 26m². 2 / kg, the 3-day flexural strength decreased by 0.5 MPa, and the 3-day compressive strength decreased by 3.1 MPa. Compared with Application Example 1, Application Example 2 showed a 3.1% increase in 45 μm sieve residue and a 28 m² decrease in specific surface area. 2 / kg, the 3d flexural strength decreased by 0.6MPa and the 3d compressive strength decreased by 3.5MPa, indicating that the mixing ratio range of the liquid grinding aid provided in this application has a good effect on improving the grinding effect of the liquid grinding aid and the strength of high alkali cement.

[0093] Compared to Application Example 1, Comparative Application Example 3 shows a 4.1% increase in sieve residue at the 45 μm sieve and a 28 m² decrease in specific surface area. 2 / kg, the 3-day flexural strength decreased by 0.9 MPa, and the 3-day compressive strength decreased by 4.7 MPa. Compared with Application Example 1, the 45 μm sieve residue in Application Example 4 increased by 4.5%, and the specific surface area decreased by 32 m². 2 / kg, the 3d flexural strength decreased by 1.1MPa and the 3d compressive strength decreased by 5MPa, indicating that there is a good synergistic effect among the components of the liquid grinding aid provided in this application, which has a good effect on improving the grinding effect of the liquid grinding aid and the strength of high alkali cement.

[0094] Compared to Application Example 1, Comparative Application Example 5 shows a 5.3% increase in 45μm sieve residue and a 34m² decrease in specific surface area. 2 / kg, the 3d flexural strength decreased by 1.2MPa and the 3d compressive strength decreased by 5.2MPa, indicating that the modified polyol amine ester provided in this application has a better grinding aid effect than the unmodified triisopropanolamine maleate.

Claims

1. A liquid grinding aid for high-alkali cement, characterized in that, The raw materials used include the following components in parts by weight: 15-25 parts modified polyol amine ester, 7-12 parts glycerol, 0.5-1.5 parts sodium chloride, 3-6 parts hydroxycarboxylate, and 60-70 parts water; The modified polyol amine ester comprises triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester, acrylic acid, initiator and chain transfer agent in a molar ratio of (13-17):(5-8):(18-22):(0.05-0.15):(0.03-0.12).

2. The liquid grinding aid for high-alkali cement according to claim 1, characterized in that: The preparation method of the modified polyol amine ester includes the following steps: S1. Disperse triisopropanolamine maleate, isobutylene alcohol polyoxyethylene ether fatty acid ester and chain transfer agent in water, stir and mix to obtain a mixed solution with a concentration of 50-55wt%. S2. Heat the mixed solution obtained in step S1 to 75-85℃, and simultaneously add an acrylic acid solution with a concentration of 60-63wt% and an initiator solution with a concentration of 15-18wt% to it. Stir the reaction for 3.5-4 hours to obtain a modified polyol amine ester solution. S3. The modified polyol amine ester solution in step S2 is filtered to obtain a crude modified polyol amine ester product, and the crude modified polyol amine ester product is washed and dried to obtain a modified polyol amine ester.

3. A liquid grinding aid for high-alkali cement according to claim 2, characterized in that: In step S2, the mixed solution is heated to 80°C.

4. A liquid grinding aid for high-alkali cement according to claim 2, characterized in that: The isobutylene alcohol polyoxyethylene ether fatty acid ester is isobutylene alcohol polyoxyethylene ether palmitate.

5. A liquid grinding aid for high-alkali cement according to claim 4, characterized in that: The preparation method of the isobutylene alcohol polyoxyethylene ether palmitate includes the following steps: I. Prepare a reaction solution by stirring and mixing isobutylene alcohol polyoxyethylene ether, palmitic acid and catalyst; II. The reaction solution obtained in step I is heated to 135-145℃ in an oil bath and subjected to vacuum distillation while stirring for 2.5-3.5 hours to obtain a crude product. The crude product is dried to constant weight to obtain isobutylene alcohol polyoxyethylene ether palmitate. The weight ratio of isobutylene alcohol polyoxyethylene ether, palmitic acid and catalyst is (12-18):(2-3):(0.1-0.15), and the catalyst is p-toluenesulfonic acid.

6. A liquid grinding aid for high-alkali cement according to claim 5, characterized in that: In step II, the reaction solution is heated to 140°C.

7. A liquid grinding aid for high-alkali cement according to claim 1, characterized in that: The hydroxycarboxylic acid salt is sodium gluconate.

8. A method for preparing a liquid grinding aid for high-alkali cement according to any one of claims 1-7, characterized in that, Includes the following steps: Modified polyol amine ester, glycerol, sodium chloride, hydroxycarboxylate and water are mixed and stirred evenly to obtain a liquid grinding aid for high alkali cement.

9. The application of the liquid grinding aid for high-alkali cement as described in claim 1, characterized in that: The liquid grinding aid used for high-alkali cement is added at a dosage of 0.04-0.06 wt% of the high-alkali cement during the high-alkali cement grinding process.

Citation Information

Patent Citations

  • Synthetic method of polyethylene glycol amine ester-carboxylic acid macromolecule grinding aid

    CN103113510A

  • Cement grinding aid and preparation method thereof

    CN112759723A